Genome-wide association analyses identify three new susceptibility loci for primary angle closure glaucoma - Simmons, Cameron (2018)
Primary angle closure glaucoma (PACG) is a major cause of blindness worldwide. We conducted a genome-wide association study including 1,854 PACG cases and 9,608 controls across 5 sample collections in Asia. Replication experiments were conducted in 1,917 PACG cases and 8,943 controls collected from a further 6 sample collections. We report significant associations at three new loci: rs11024102 in PLEKHA7 (per-allele odds ratio (OR)=1.22; P=5.33×10(-12)), rs3753841 in COL11A1 (per-allele OR=1.20; P=9.22×10(-10)) and rs1015213 located between PCMTD1 and ST18 on chromosome 8q (per-allele OR=1.50; P=3.29×10(-9)). Our findings, accumulated across these independent worldwide collections, suggest possible mechanisms explaining the pathogenesis of PACG.